Analisis Penerapan Green Accounting dan Dampaknya terhadap Laba Usaha - Baiq Nurul Wiranti (SAFE-Network, 2023)
Indonesia is included in the top five countries whose industrial sector is quite high, so that Indonesia is known as an industrial country. It is undeniable that the industrial sector creates various problems for the environment such as water and air pollution, production waste and social inequality in the environment. Green accounting is an accounting concept that emphasizes the balance between business objectives, namely obtaining profit and environmental objectives, namely environmental sustainability itself. The purpose of this study is to describe how the implementation of green accounting at PT ABC and whether the application has an impact on PT ABC's operating profit. This research was conducted using qualitative methods with a descriptive approach. Data collection by researchers is by way of observation, interviews and documentation. Informants in this study were production managers, SPV accounting and the community around the factory. The results of this study indicate that PT ABC has carried out its responsibility towards the surrounding environment by incurring costs related to environmental activities. The costs incurred are environmental prevention costs and internal failure costs. The application of green accounting at PT ABC has a positive impact on company profits. Although an increase in company profits may not occur immediately, with a strong commitment to sustainable practices, companies can obtain greater and more sustainable financial benefits in the future.